Profilaxia da infecção por vírus sincicial respiratório: estudo clínico prospectivo de crianças submetidas ao uso de palivizumabe - Monteiro, Ana Isabel Melo Pereira [UNIFESP] (2012)
Respiratory Syncytial Virus (RSV) is the most important etiologic agent in acute lower respiratory tract infections (ALRTIs) in children under two years, with high rates of hospitalization and death in high risk children for severe RSV infection. Objective: To identify the virus present in acute respiratory tract infections (ARTIs) and to analyze rates of hospitalization and death in children who received palivizumab prophylaxis. Methods: Prospective cohort of 198 infants up to 1 year old born before 29 weeks gestation and infants less than two years of age with hemodynamically instable cardiopathy or chronic pulmonary disease, who received prophylactic palivizumab against severe RSV infections in 2008. During this period, a nasopharyngeal aspirate (NPA) was collected in each episode of ARTI for identification of RSV, adenovirus, parainfluenza 1, 2 and 3, influenza A and B by direct immunofluorescence, and rhinovirus and metapneumovirus for RT-PCR. Data regarding hospitalization and death were collected. Results: Of the 198 infants included, 117 (59,1%) presented ARTIs, with a total of 175 episodes. Of 76 NPAs collected, 35 were positive, being rhinovirus (75.7%), RSV (18.9%), parainfluenza (8.1%), adenovirus 2 (2.7%), metapneumovirus (2.7%) and 3 samples presented multiple agents. Of 48 hospitalizations, 18 presented respiratory causes, but in only one child was found RSV. None of the 2 children who died had RSV. Conclusion: During the palivizumab prophylaxis period, the frequency of RSV detected in high risk children with ARTIs and those who were hospitalized was low.